(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Endothelin receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Endothelin Receptors [24]) are activated by the endogenous 21 amino-acid peptides endothelins 1-3 (endothelin-1, endothelin-2 and endothelin-3).